Financial Sustainability Perusahaan BUMN Sektor Transportasi Laut: DER Sebagai Variabel Mediasi - Wahid, Moh; Putra Prasetya, Bangun (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The concept of sea toll is one of the maritime transportation programs or strategies implemented by the government in improving inter-island relations and supporting economic growth. So that financial sustainability is important related to the sustainability of the policy. This study uses an independent variable, namely Return On Assets (ROA) with a dependent variable Financial Sustainability with Debt To Total Equity (DER) as a mediation variable. The purpose of this study is to see the effect of Debt To Total Equity (DER) in mediating the variable Return On Assets (ROA) on Financial Sustainability. This research uses the object of research of state-owned companies engaged in sea transportation, namely PT. PELNI and PT. ASDP. Data is obtained from financial statements. The results show that the result of two-tailled probality value is 0.20127969 > 0.05. The results can be concluded that Debt to Total Equity (Z) does not mediate Return on Asets (ROA) to financial sustainability.